2021
DOI: 10.4251/wjgo.v13.i5.424
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of curative liver resection for hepatocellular carcinoma in patients with cirrhosis

Abstract: BACKGROUND Given the poor synthetic function of cirrhotic liver, successful resection for patients with hepatocellular carcinoma (HCC) necessitates the ability to achieve resections with tumor free margins. AIM To validate post hepatectomy liver failure score (PHLF), compare it to other established systems and to stratify risks in patients with cirrhosis who underwent curative liver resection for HCC. METHODS Between December 2010 and January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The MELD score is traditionally used for patients with decompensated cirrhosis on the waiting list for LT [3][4][5][6]. However, multiple studies have reported that higher MELD scores are associated with poor outcomes of patients with HCC undergoing LR [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The MELD score is traditionally used for patients with decompensated cirrhosis on the waiting list for LT [3][4][5][6]. However, multiple studies have reported that higher MELD scores are associated with poor outcomes of patients with HCC undergoing LR [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extremely high preoperative α-fetoprotein level was associated with increased rates of R1 resection and vascular invasion (67). In another report, preoperative model of end-stage liver disease, grade of post hepatectomy liver failure and HCC recurrence were independent predictors for patient survival (68).…”
Section: Important Considerationsmentioning
confidence: 98%
“…However, several aspects could be enhanced or explored further[ 3 ]. First, while the present study effectively established the predictive value of the NLR, Fib4 levels, and APRI, it primarily focused on a retrospective patient cohort.…”
Section: To the Editormentioning
confidence: 99%